Effect of Thermal Manipulation During Embryonic Development on Internal and External Quality Characteristic of Quail Eggs - Deeb, Eiad Reiad Ali; Mohrah, Ibrahim; سكرية, شادي (Journal of agricultural, environmental and veterinary sciences, 2021)
Lately, quail egg production has developed as a good resource for animal protein to provide the people requirements of that protein, in addition, the quail egg has some specifications that better than chicken eggs like its content of proteins, vitamins and amino acids. The research aimed to determine the influence of thermal manipulation during embryonic development on the egg quality of the fresh egg. 200 eggs were divided into four equal groups. Eggs of the first group (control) incubated under the standard terms for incubation of quail eggs, and the eggs of other groups were incubated under 41° C for three hours in three consecutive days of different periods of embryonic development (early, late, and dual period). 40 eggs were collected randomly from groups (10 eggs from each) to study the internal and external indications of quail egg quality.The results showed up superiority significantly (p
Keywords: quail eggs; thermal manipulation; internal and external egg specification